Mistakes in the management of iron deficiency anaemia: a narrative review - Madunil Anuk Niriella; Hiruni Jayasena; Achini Withanachchi; Anuja Premawardhena (Hematology)
Introduction Anaemia occurs due to an imbalance between erythrocyte production and loss. This imbalance can be due to ineffective erythropoiesis, blood loss or haemolysis. Whilst there are many causes for anaemia, iron deficiency anaemia (IDA) remains the predominant cause worldwide.Areas covered There have been many updated guidelines on the management of IDA in the past few years. As the reasons for IDA are many, evaluation requires thorough analysis and focused investigations. As an asymptomatic disease in the early stages, IDA can lead to many mistakes in its management. This review highlights potential mistakes in assessing and managing IDA and recommendations to avoid them.Conclusion The effective management of IDA necessitates a comprehensive and multidisciplinary approach. By recognising and addressing the common mistakes highlighted in this narrative review, healthcare professionals can improve patient outcomes, minimise complications, and enhance the overall quality of care.